CHARACTERISTICS ANALYSIS OF EMPLOYER BRAND ATTRACTIVENESS ON INDONESIAN GRADUATE BUSINESS SCHOOL STUDENTS - , Niken Lulianti Rahayu, Drs. Gugup Kismono, M.B.A, Ph.D., MM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed to observe the characteristics dimensions of employer brand and its career goal items. It also intended to identify employer branding communications that were attractive to them. It examined their differences based on respondents characteristics. While many previous studies had been done in Western environments and several developed countries in Asia, the research had not yet been done in Indonesia using samples from Indonesian graduate school students. A quantitative research design and methodology was adopted to conduct the research. The research relied on quantitative measures through self-administered questionnaire and qualitative measures through open-ended survey items. Data were collected from October through November 2011. The sample consisted of 85 male and 61 female respondents. There were 16 items used to represent the attractiveness dimensions of employer branding. The items were confirmed to have adequate validity and reliability. Analysis on the research results showed that there were various significant items across the respondents characteristics (gender, age, marital status, academic achievement, working experience, and economic background). The differences between each group for the most and the least important dimension can still be observed. However, the results of all ANOVA Test for each respondent characteristics were not statistically significant. The Remuneration and Advancement Opportunities (RAO) and Job Characteristics (JC) dimensions appear to be the most favored while the Employer Reputation and Image (ERI) dimension has constantly appeared as the least important dimension among the groups. The findings for career goals items are generally consistent with the known theories of organizational attraction. Nonetheless, although there are several emphasis in utilizing the different communication channels to attract the target talents, combinations of the channels are still recommended. The investigation of the attractiveness dimensions establishes an initial framework for organizations about where to start building their employer brand when dealing with Indonesian graduate students. Organizations can specifically target potential employees by managing the dimensions mix based on empirical findings. However, consistency or alignment between the employer brand image with the employment experience should be maintained by the organizations to successfully build the employer brand and promote loyalty and commitment.